Does Third-Party Intervention Matter? A Video-Based Analysis of the Effect of Third-Party Intervention on the Continuation of Interpersonal Conflict Behaviour - Ejbye-Ernst, Peter (The British journal of criminology, 2023)
The article investigates whether third-party intervention influences the continuation of antagonist conflict behaviour in interpersonal conflicts. The analysis is based on a systematic coding of video footage of real-life conflicts from the streets of Amsterdam. A panel data analysis shows that intervention leads to discontinuation of conflict behaviour. The analysis furthermore finds that while physically forceful intervention stops conflict behaviour, expressions of disapproval have no noticeable effect. The social relationship between third parties and antagonists does not appear to matter for this effect. Third parties thus play an integral part in the development of interpersonal conflicts, but this influence depends on how they intervene. Future preventive efforts should emphasize that intervention works but must be performed in certain ways to be effective.